2020
DOI: 10.3390/ijms21051672
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibitory Actions of Multitargeted Tyrosine Kinase Inhibitors on Different Ionic Current Types in Cardiomyocytes

Abstract: Lapatinib (LAP) and sorafenib (SOR) are multitargeted tyrosine kinase inhibitors (TKIs) with antineoplastic properties. In clinical observations, LAP and SOR may contribute to QTc prolongation, but the detailed mechanism for this has been largely unexplored. In this study, we investigated whether LAP and SOR affect the activities of membrane ion channels. Using a small animal model and primary cardiomyocytes, we studied the impact of LAP and SOR on Na + and K + currents. We found that LAP-induced QTc prolongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…It is reasonable to presume that, apart from its effects on the viral polymerase and the proofreading exoribonuclease (Agostini et al, 2018;Brown et al, 2019;Tchesnokov et al, 2019;Gordon et al, 2020), to what extent RDV-induced perturbations of ion channels unexpectedly identified in this study participates in its antiviral actions has yet to be further delineated. Our results are in accordance with previous findings demonstrating that the large hyperpolarization induced inward currents (i.e., I MEP ) occur in glioma cells, heart cells, pituitary cells, and macrophages (Dyachok et al, 2010;Liu et al, 2012;So et al, 2013;Chiang et al, 2014;Chang et al, 2020a;Chang et al, 2020b). Such hyperpolarization-induced activation followed by irregular time course indicates that I MEP was produced by transient rupture of cell membrane caused by the electrical field tied to large hyperpolarization (Dyachok et al, 2010;Wu et al, 2012;So et al, 2013;Chang et al, 2020a;Chang et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is reasonable to presume that, apart from its effects on the viral polymerase and the proofreading exoribonuclease (Agostini et al, 2018;Brown et al, 2019;Tchesnokov et al, 2019;Gordon et al, 2020), to what extent RDV-induced perturbations of ion channels unexpectedly identified in this study participates in its antiviral actions has yet to be further delineated. Our results are in accordance with previous findings demonstrating that the large hyperpolarization induced inward currents (i.e., I MEP ) occur in glioma cells, heart cells, pituitary cells, and macrophages (Dyachok et al, 2010;Liu et al, 2012;So et al, 2013;Chiang et al, 2014;Chang et al, 2020a;Chang et al, 2020b). Such hyperpolarization-induced activation followed by irregular time course indicates that I MEP was produced by transient rupture of cell membrane caused by the electrical field tied to large hyperpolarization (Dyachok et al, 2010;Wu et al, 2012;So et al, 2013;Chang et al, 2020a;Chang et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
“…To study whether RDV possibly perturb this type of ionic current, we bathed cells in Tyrode's solution (Ca 2+ -free) and performed whole-cell current recordings. As described in previous observations (Dyachok et al, 2010;Wu et al, 2012;Chang et al, 2020a;Chang et al, 2020b), when the cell was voltage-clamped at −80 mV and the 300-ms hyperpolarizing pulse to −200 mV was applied to evoke I MEP . As depicted in Figures 9A, B, when cells were continually exposed to RDV, the amplitude of I MEP elicited by such large hyperpolarization was progressively raised.…”
Section: Stimulation By Rdv Of I Mep In Gh 3 Cellsmentioning
confidence: 96%
“…Furthermore, in the continued presence of SSM (3 µM), the subsequent addition of either tefluthrin (10 µM) or telmisartan (10 µM) was effective in reversing the SSM-induced inhibition of peak I Na . [20,[30][31][32][33]. As shown in Figure 2, SSM or SesA, at a concentration of 3 μM, produced inhibitory effects on the peak amplitude of INa.…”
Section: Comparison Between Effects Of Ssm Sesa Ssm Plus Tefluthrinmentioning
confidence: 80%
“…They were immersed at room temperature (20-25 • C) in normal Tyrode's solution, the composition of which is elaborated above. We measured ion currents in the whole-cell model of a standard patch-clamp technique with dynamic adaptive suctioning (i.e., decremental change of suction pressure in response to a progressive increase in the electrode resistance), with the aid of an RK-400 (Bio-Logic, Claix, France) or an Axopatch-200B (Molecular Devices, Sunnyvale, CA) patch amplifier [33,38,58]. The microelectrodes used were prepared from Kimax-51 borosilicate capillaries with a 1.5-mm outer diameter (#34500; Kimble; Dogger, New Taipei City, Taiwan) by using a PP-830 vertical puller (Narishige, Taiwan Instrument, Taipei, Taiwan).…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%
“…Recently, it was reported that lapatinib suppressed I Ks , I Kr , and I K1 , but not I Ca , and suppressed the amplitude of peak I Na , with IC 50 values of 1.84 µmol/L and 0.8 µmol/L, against I Ks and I Kr , respectively. Furthermore, the QTc (corrected QT) prolongation mediated by lapatinib was reversed by isoproterenol (an activator of I Ks ) in mice [27,28], which may explain the more significant decrease in the rate observed with WT-hiPSC-CMs than with LQT-hiPSC-CMs, to a certain degree.…”
Section: Discussionmentioning
confidence: 99%